Thermal Decomposition of Pure Waste and Binary Mixtures - Thalyne de Almeida Ferreira Rocha; Guilherme Henrique Alves Pinto; Maria do Carmo Ferreira; Jose Teixeira Freire; Fábio Bentes Freire (Fine Chemical Engineering, 2024)
In this study, the thermal decomposition of pure organic residues - coffee grounds, sugarcane bagasse and orange juice residues - and their binary mixtures with coffee grounds were analyzed. The results of thermogravimetric analyses at 10 °C/min under an oxidizing atmosphere showed that sugarcane bagasse and coffee grounds had individually higher reaction rates in the devolatilization zone, while orange juice residues burned more quickly in the combustion zone. There were significant mass interactions between the coffee grounds and orange juice residues in the binary mixtures, which led to higher reaction rates in the combustion of the mixture than in the pure residues. In the mixture of coffee grounds and sugarcane bagasse, there were no significant mass interactions. These encouraging findings can optimize the generation of bioenergy from these wastes and their mixtures, therefore, one must understand the different interactions during thermal decomposition to then develop sustainable strategies for utilizing biomass.